In vivo electrophysiological study of the targeting of 5‐HT3 receptor‐expressing cortical interneurons by the multimodal antidepressant, vortioxetine. (3rd March 2022) - Schweimer, Judith V.; Brouard, Julia T.; Li, Yan; Sánchez, Connie; Sharp, Trevor
Abstract: The antidepressant vortioxetine has high affinity for the ionotropic 5‐HT3 receptor (5‐HT3 R) as well as other targets including the 5‐HT transporter. The procognitive effects of vortioxetine have been linked to altered excitatory:inhibitory balance in cortex. Thus, vortioxetine purportedly inhibits cortical 5‐HT3 R‐expressing interneurons (5‐HT3 R‐INs) to disinhibit excitatory pyramidal neurons. The current study determined for the first time the effect of vortioxetine on the in vivo firing of putative 5‐HT3 R‐INs whilst simultaneously recording pyramidal neuron activity using cortical slow‐wave oscillations as a readout. Extracellular single unit and local field potential recordings were made in superficial layers of the prefrontal cortex of urethane‐anaesthetised rats. 5‐HT3 R‐INs were identified by a short‐latency excitation evoked by electrical stimulation of the dorsal raphe nucleus (DRN). Juxtacellular‐labelling found such neurons had the morphological and immunohistochemical properties of 5‐HT3 R‐INs: basket cell or bipolar cell morphology, expression of 5‐HT3 R‐IN markers and parvalbumin‐immunonegative. Vortioxetine inhibited the short‐latency DRN‐evoked excitation of 5‐HT3 R‐INs and simultaneously decreased cortical slow wave oscillations, indicative of pyramidal neuron activation. Likewise, the 5‐HT3 R antagonist ondansetron inhibited the short‐latency DRN‐evoked excitation of 5‐HT3 R‐INs. However unlike vortioxetine, ondansetron did not decrease cortical slow‐wave oscillations, suggesting a dissociation between this effect and inhibition of 5‐HT3 R‐INs. The 5‐HT reuptake inhibitor escitalopram had no consistent effect on any electrophysiological parameter measured. Overall, the current findings suggest that vortioxetine simultaneously inhibits (DRN‐evoked) 5‐HT3 R‐INs and excites pyramidal neurons, thereby changing the excitatory:inhibitory balance in cortex. However, under the current experimental conditions, these two effects were dissociable with only the former likely involving a 5‐HT3 R‐mediated mechanism. Abstract : We investigated the effects of the novel antidepressant, vortioxetine, on extracellular single unit recordings from 5‐HT3 R‐expressing interneurons in the superficial layers of the prefrontal cortex (PFC) of urethane‐anaesthetised rats. 5‐HT3 R‐interneurons were identified by a short‐latency excitation evoked by electrical stimulation of the dorsal raphe nucleus (DRN). Vortioxetine inhibited the short‐latency DRN‐evoked excitation of 5‐HT3 R‐interneurons. Juxtacellular labelling found that the putative interneurons had the morphological and immunohistochemical properties of 5‐HT3 R‐interneurons.